Mortalité du naissain d’Huître creuse Crassostrea gigas dans l’étang de Thau en 2009 - Pernet, Fabrice; Barret, Jean; Le Gall, Patrik; Malet, Nathalie; Pastoureaud, Annie; Munaron, Dominique; De Lorgeril, Julien; Bachere, Evelyne; Vaquer, Andre; Huvet, Arnaud; Corporeau, Charlotte; Normand, Julien; et al. (2010)
This study was conducted in the Mediterranean area during a mass mortality event of Pacific oyster Crassostrea gigas. The objectives of this work were to increase our understanding of the mass mortality phenomena in Pacific oysters, to identify risky cultivation practises and to propose mitigation strategies. In the first part of this work, we followed environmental parameters of the Thau lagoon in relation with mortality events. Then, we compared mortality and growth parameters of oysters as a function of their origins, their development stages and cultivation sites in relation with energetic, reproduction and pathogens. Finally, we conducted transfer experiments where oysters maintained free of mortality in open sea were transferred in the Thau lagoon where mass mortality occurred. From the environmental standpoint, we showed that mortality of oysters in the Thau lagoon occurred during years where phytoplankton levels are low (2008-09) compared to averaged values recorded in 1996-2007. Mortality of oysters specifically hit one year-old animals irrespective of their origins and ploidy levels, when seawater temperature reached 17.5°C. Compared to the two previous years, mortality has increased and temperature threshold decreased of ~2°C. Mortality of one year-old oysters coincides with accelerated growth rates and energetic weakness. In contrast to the well known summer mortality model developed during the Morest project, mortality in 2009 was observed while oysters were at the onset of gametogenesis which suggests that reproductive effort is not pivotal. Mortality also coincides with elevated viral load of the OsHV-I herpes in oysters, so that virus may have played a major role in this mortality event. Finally, our study show that oysters maintained in open sea at 22m deep exhibited no mortality. However, when these animals were transferred into the Thau lagoon in spring, mortality reached 84% after only 18 d. This mortality event again coincided with a massive infection by the virus herpes. From a practical ...